ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN CAFE TUGU LIMAU DI KECAMATAN TEBAS KABUPATEN SAMBAS - Mariska, Mariska; Purwaningsih, Endang; Syahrudin, Husni (Universitas Tanjungpura, 2023)
This thesis entitled Quality of Service to Customer Satisfaction Cafe Tugu Limau in Mekar Sekuntum Village, Tebas District, Sambas Regency. Problem general in this research is How the Quality of Service Against Customer Satisfaction of the Tugu Limau Cafe in Mekar Sekuntum Village, District Tebas, Sambas Regency, with its sub-problem, How is Quality Tangible Services, Reliability, Responsiveness or Concern (Responsiveness), Empathy (Empathy) and Insurance (Assurance). perceived and expected by consumers of the Tugu Limau Cafe in Mekar Village Sekuntum of Tebas District, Sambas Regency? Research approach that used is a qualitative approach with descriptive research methods. Data collection techniques used are Interview Techniques, and Documentation. The data collection tools are observation guidelines, guidelines interviews, field notes and cameras. Cafe Tugu Limau informant namely Sisters Sholeha, Nopia, Melin, and Brother Haider. Research Results Show that Service Quality has been realized in terms of Service Quality tangible, namely the availability of public facilities in physical form such as tables, chairs and others, in terms of service quality Reliability (Reliability), visible with availability in directing and assisting consumers, in terms of Responsiveness or Concern (Responsiveness) services provided quickly and appropriate, in terms of Empathy (Empathy) attitude and service behavior that given shows a sense of care and in terms of insurance (assurance) looks visitors feel comfortable when in the Cafe. and has shown it is consumer satisfaction.